A Qualitative Model of the Indicators and Components of Internal Marketing, Organizational Intelligence, and Organizational Innovation in the Tax Administration of Iran - Taheri, Esmat Sadat; Fattahi, Majid; Aghajani, Hassanali (Management Strategies and Engineering Sciences, 2024)
Today, marketing has become a fundamental and essential element for the success of both profit and non-profit organizations. Given the continuously changing environment and the increasing number of uncontrollable external factors and threats in the market, mere gradual improvement is no longer sufficient. All organizations and companies need to move toward creativity and innovation to ensure their survival and active presence in the market. On the other hand, the aim of organizational intelligence is to accelerate the decoding and transfer of organizational knowledge, identify opportunities, and solve business problems more quickly than in the past. This study aims to propose a qualitative model of the indicators and components of internal marketing, organizational intelligence, and organizational innovation in the Tax Administration of Iran. The research is applied in purpose and uses a thematic analysis method. The sampling method was snowball sampling, and the main data collection method was conducting in-depth interviews with 15 experts, managers, and specialists in the fields of marketing and tax administration until theoretical saturation was reached. The thematic analysis process, following the approach provided by Braun and Clarke (2006), was conducted in six stages. Initially, 213 primary codes were obtained, and after removing duplicate codes, 35 selective codes were extracted. By aggregating the selective codes into broader semantic domains, six main and sub-themes were identified and named. The data were analyzed using MAXQDA software, both separately and in general. In the findings, two sub-themes and 13 basic themes were identified for internal marketing, two sub-themes and 10 basic themes for organizational innovation, and two sub-themes and 11 basic themes for organizational intelligence.